2016
DOI: 10.1016/j.mayocp.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasonography for Primary Care Physicians and General Internists

Abstract: Point-of-care ultrasonography (POCUS) is a safe and rapidly evolving diagnostic modality that is now utilized by health care professionals from nearly all specialties. Technological advances have improved the portability of equipment, enabling ultrasound imaging to be executed at the bedside and thereby allowing internists to make timely diagnoses and perform ultrasound-guided procedures. We reviewed the literature on the POCUS applications most relevant to the practice of internal medicine. The use of POCUS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 136 publications
(178 reference statements)
6
151
0
6
Order By: Relevance
“…13 Similar to other studies, they reported that barriers to performing POCUS include the experience and skill of the individual performing the ultrasound examination, availability of training, financial costs, lack of standardized templates for documentation, policies for billing, quality assurance for competency, and image archiving. 13 Another surprising result from this study was that approximately 28% of respondents performed only one ultrasound examination per shift. The safety record of EM-POCUS is very high and we should be substituting less harmful imaging studies such as ultrasound instead of more harmful imaging studies involving ionizing radiation.…”
Section: Discussionsupporting
confidence: 67%
“…13 Similar to other studies, they reported that barriers to performing POCUS include the experience and skill of the individual performing the ultrasound examination, availability of training, financial costs, lack of standardized templates for documentation, policies for billing, quality assurance for competency, and image archiving. 13 Another surprising result from this study was that approximately 28% of respondents performed only one ultrasound examination per shift. The safety record of EM-POCUS is very high and we should be substituting less harmful imaging studies such as ultrasound instead of more harmful imaging studies involving ionizing radiation.…”
Section: Discussionsupporting
confidence: 67%
“…[1][2][3] Evidence supports the idea that adding POCUS to the examination of selected patients leads to improved and earlier diagnosis in a hospital setting. [4][5][6][7] As a result, POCUS has been integrated into the curriculum in several medical schools 8,9 and medical specialist training programs. 10,11 General practitioners are increasingly using POCUS in patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Despite the undisputed advantages of utilizing POCUS, there are several barriers to consider due to challenges related to equipment and technology, experience and skills of the operator(s), availability of documentation templates, electronic storage capability for image archiving, and policies and procedures for quality assurance and billing. [3] …”
Section: Introductionmentioning
confidence: 99%